Minting Anomalies in Greek Sicily: Stepped Flans, Edge Ridges, and Edge Splits - Daehn, William E. (KOINON: The International Journal of Classical Numismatic Studies, 2023)
Numismatists have long sought to gain a better understanding of ancient Greek minting techniques, a subject for which no ancient written sources have survived. Although the topic has been the subject of numerous papers, some of these have been based more on speculation than on evidence. Fortunately, several researchers have conducted useful experiments in re-creating ancient minting techniques, and some of these have been quite informative.